2016
DOI: 10.3168/jds.2015-9916
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Lactobacillus plantarum strain that ameliorates chronic inflammation and metabolic disorders in obese and type 2 diabetic mice

Abstract: In this study, we identified a strain of lactic acid bacteria (LAB) that induces high levels of IL-10 production by immune cells, and evaluated the ability of the strain to suppress chronic inflammation and ameliorate metabolic disorders in in vitro and in vivo models. Among a collection of LAB strains, Lactobacillus plantarum strain OLL2712 (OLL2712) induced the highest levels of IL-10 production in mouse-derived dendritic cells and peritoneal macrophages. The anti-inflammatory effects of this strain were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 50 publications
3
42
0
6
Order By: Relevance
“…These results suggest that OLL2712 stimulation of immune cell IL-10 production depends on MyD88 and TLR2. In addition, we confirmed that OLL2712 cells cultured statically for 18 h in de Man, Rogosa, and Sharpe (MRS) broth, which we had used in a previous study (15), exhibited higher levels of IL-10 and IL-12 production than 8-h (ϩ) cells.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…These results suggest that OLL2712 stimulation of immune cell IL-10 production depends on MyD88 and TLR2. In addition, we confirmed that OLL2712 cells cultured statically for 18 h in de Man, Rogosa, and Sharpe (MRS) broth, which we had used in a previous study (15), exhibited higher levels of IL-10 and IL-12 production than 8-h (ϩ) cells.…”
Section: Resultssupporting
confidence: 65%
“…Here, the bacterial cells cultured for 8 h, 14 h, and 16 h with Q-17S are described as 8-h (ϩ), 14-h (ϩ), and 16-h (ϩ) cells. We examined the effect of culture phases and adding Q-17S on the immunomodulatory properties of MEP222801, an L. plantarum strain with high IL-10-inducing activity second to OLL2712 in our LAB library (15), and obtained almost the same result as OLL2712 (Fig. 2).…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations